2017
DOI: 10.1039/c7ra00370f
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti-tubulin agents from plant and marine origins: insight from a molecular modeling and dynamics study

Abstract: The screening of a variety of botanical species and marine organisms provided satisfactory novel tubulin binding agents (TBAs). The current study aims to quantify the binding capabilities of several TBAs including vinca alkaloids, colchicine and other taxol-domain binding agents with microtubule. The stability of the bound complexes and detailed interactions within the active site are the endeavor of the study. Different natural extracts reported as TBAs, have been screened against the refined structure of ab-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This knowledge can be used to search for and synthesize new active compounds with specific properties. Based on available experimental data about the inhibition of tubulin polymerization, in recent years there have been many studies related to the molecular modelling and docking of various classes of chemical compounds in the colchicine‐binding site of tubulin …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge can be used to search for and synthesize new active compounds with specific properties. Based on available experimental data about the inhibition of tubulin polymerization, in recent years there have been many studies related to the molecular modelling and docking of various classes of chemical compounds in the colchicine‐binding site of tubulin …”
Section: Introductionmentioning
confidence: 99%
“…Based on availablee xperimental data about the inhibition of tubulin polymerization, in recent years there have been many studies related to the molecular modelling and dockingo fv arious classes of chemical compounds in the colchicine-binding site of tubulin. [41][42][43][44][45][46][47][48][49] In one of the first studies [41,42] devotedt ot he docking of various ligandsi nto the colchicine-binding site of tubulin,i th as been shown that the binding of colchicine derivatives to the active site of a-tubulini sd ue to the formation of hydrogen bonds of colchicines with residues such as His28, Ser232, Cys356, and Arg320. For b-tubulin, binding occursw ith Thr33 and Tyr36.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the flow cytometry patterns observed in Figure 3, the intrinsic pathway is the predominant apoptosis mechanism in the human cancer cells evaluated here. Several studies have reported that diterpenes, especially those with cembrane and briarane scaffolds, have anti‐tubulin activity (Shaaban et al., 2019; Yadava et al., 2017), inducing cell death thorough this mechanism. In order to determine whether the observed apoptosis and cell death could be generated by the interaction with microtubules, an interaction study based on NMR measurements and computational calculations was performed and will be presented in the following sections.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the number of contacts between the H9/M-loop regions of β1 and H3 of β2 decreased slightly. This may explain why the antitumor activities of 1 and 2 , although all IC 50 values are in the nanomolar range, are not as strong as those of paclitaxel and epothilones. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the toxicity of 1 is disappointing, the antiangiogenic effect and the activity against neurodegeneration and autoimmune disorders of 2 maintain hopes for the development of clinical uses of these MSAs. Very recent excellent reviews and full papers summarize these studies. …”
Section: Introductionmentioning
confidence: 99%